Effect of mixed protein supplementation on golf performance and muscle function: a randomized, double-blind, placebo-controlled study - Ji-Won Seo; Shu Jiang; Soyoung Ahn; Yu Seon Kang; Yunho Sung; Xinxing Li; Parivash Jamrasi; Eun Mi Sun; Jihee Yoo; Byung-Yong Kim; Hyunsu Sim; Wook Song (Taylor & Francis Group, 2024)
Background As a relatively novel approach to enhancing skeletal muscle health, mixed protein supplementation has shown similar responses to whey protein. However, no previous studies have examined its impact on golf swing performance. This study aimed to examine the effect of mixed protein supplementation on the swing performance and muscle strength of casual golfers.Methods Sixty participants with a handicap of less than 20 were recruited and randomly assigned to a double-blind, placebo-controlled study design. The participants were divided into two groups: a mixed protein group (MG, n = 30), and a placebo control group (CG, n = 30). They were instructed to ingest either a supplement containing casein calcium, whey protein, and isolated pea protein, or a placebo, once daily for 8 weeks. Pre- and posttests consisted of anthropometric measurements, muscle strength (isokinetic knee and trunk strength, and handgrip strength), 2-minute push-ups, balance, and golf swing performance using a driver and 7-iron.Results After the 8-week supplementation period, ANCOVA, using baseline values as covariates, revealed significant differences for driver distance (p = .004) and driver ball speed (p < .001). MG significantly increased driver distance by 5.17 ± 12.8 m (p = .046), driver ball speed by 1.36 ± 2.87 m/s (p = .021). Additionally, significantly improvements were observed in hand grip strength (+2.12 ± 3.47 kg, p = .004), two-minute push-ups (+4.89 ± 8.14 reps, p = .004), and balance score (−0.37 ± 0.69 min, p = .009). No significant differences were observed in body composition parameters (p > .05).Conclusion The intake of a mixed protein containing both animal and plant proteins had positive effects on golf performance and muscle function. Therefore, mixed proteins may represent a safe and effective approach to enhancing skeletal muscle health in golf players.